Pengembangan Buku Bacaan Berbasis Karakter untuk Meningkatkan Kemampuan Membaca Siswa di Kelas 3 SD Muhammadiyah 18 Medan - Novia Ramadhani; Salminawati , Salminawati; Andina Halimsyah Rambe (Jurnal Bintang Pendidikan Indonesia, 2025)
The research that has been carried out is entitled "Development of Character-Based Reading Books to Improve Reading Ability". The development of reading books as a medium to support learning has a wide relationship between writing, pictures, and others. This character-based reading book contains a brief text narrative that is connected to colored pictures and vocabulary that can be conveyed through illustrations and text. This research is a type of RND research using the ADDIE model. This research model is the ADDIE development model, namely (1) Analyze (2) Design (3) Develop (4) Implement (5) Evaluate. The results of the study show that (1) character-based reading books to improve the reading ability developed, data were obtained from media expert validators with a percentage of 80% in the valid category, material expert validators with a percentage of 80% in the valid category and linguist validators with a percentage of 80% in the valid category, (2) The results of the student response questionnaire obtained data on the percentage of responses from students of the limited test in grade III of SD Muhammadiyah 18 Medan, with a percentage of 88% in the very practical category and a large group test of 91.4. Thus, the illustrated storybook developed is practical (3) The effectiveness of the reading book is seen from the test results and data obtained from the results of the field test in grade III of SD Muhammadiyah 18 Medan, with an average percentage of N Gain students of 84% in the Effective.